Operational planning bussiness of slimmingfique - Elliza Kusumaningrum; Rhian Indradewa (Junal Ilmu Manajemen, 2023)
Awareness of healthy lifestyles continues to increase by 19% year on year and this is good news for Indonesia. The results of a survey conducted by a company Brand Meals Although there is an increase in Indonesian awareness of healthy lifestyles, the fact is that the obesity rate in Indonesia is quite high. Slimmingfique is a clinic that started up against the backdrop of the difficulty of addressing the problem of obesity. Most people who undergo a slimming program fail because of the absence of a support system. Slimmingfique is a slimming center that invites an individual to live a healthy lifestyle that results in an ideal weight, accompanied by several experts, namely general practitioners, nutritionists, psychiatrists, and personal trainers in running the program. This study aims to explain the operational planning of the slimmingfique business from operation design, operation delivery, and operational cost projection. Slimmingfique provides supplement products and consulting services for obese people with various programs designed to help them lose weight. The business also designed an app that can be used by users to monitor during the program as well as help with communication with slimmingfique trainers.